Creative expressiveness in childhood writing predicts educational achievement beyond motivation and intelligence: A longitudinal, genetically informed study. (17th May 2021) - Toivainen, Teemu; Madrid‐Valero, Juan J; Chapman, Robert; McMillan, Andrew; Oliver, Bonamy R.; Kovas, Yulia
Abstract : Background: Creativity is linked with educationally relevant constructs such as achievement, intelligence, and motivation. However, very few studies have explored longitudinal links between the constructs or the aetiology of individual differences in childhood creativity. Aims: The study addresses the gap in the literature of developmental studies on the relationship of creativity with other educationally relevant measures. Additionally, the present study is the first adequately powered genetically informative analysis of childhood creativity. Sample(s): The present study utilized data from 1, 306 twins, a subsample from a longitudinal, representative twin sample in the UK. Methods: Creativity was operationalised as a Creative Expressiveness score, using the Consensual Assessment Technique on stories written by 9‐year‐olds. Intelligence and writing motivation were assessed at age 9. Academic achievement was collected at ages 9, 12, and 16. Results: Creative Expressiveness was associated with intelligence and motivation, all measured at age 9. It also predicted variance in English grades at ages 9 and 16. The associations were weak, but significant, over and above intelligence, motivation, and earlier English grades. The variance in Creative Expressiveness was explained by genetic (35%), shared environmental (21%), and non‐shared environmental (45%) influences. The phenotypic correlations with other study variables were mainly mediated genetically. Conclusions: The results provide information that can be used for planning educational content. First, creativity can be detected in childhood writing. Second, childhood creativity may be overlooked in early educational assessments. Third, the results from the genetic analyses are important indications on the role of environments in the development of creativity.